2021
DOI: 10.1186/s12934-021-01673-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (−)−deoxypodophyllotoxin and (−)−epipodophyllotoxin via a multi-enzyme cascade in E. coli

Abstract: Background The aryltetralin lignan (−)−podophyllotoxin is a potent antiviral and anti-neoplastic compound that is mainly found in Podophyllum plant species. Over the years, the commercial demand for this compound rose notably because of the high clinical importance of its semi-synthetic chemotherapeutic derivatives etoposide and teniposide. To satisfy this demand, (−)−podophyllotoxin is conventionally isolated from the roots and rhizomes of Sinopodophyllum hexandrum, which can only grow in few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…This six-step strategy produced 8.3 mg L À1 (À)-epipodophyllotoxin with 10% conversion. 32 Besides enzyme engineering and pathway optimization in vitro, engineering the supply and recycling of cofactors, which participate in many intracellular metabolic processes and reactions, is also a feasible way to enhance PTOX production. In 2022, on the basis of pathway optimization in yeast S. cerevisiae, ) reached gram-level production in the fedbatch fermentation, which has a considerable production potential at present 33 (Fig.…”
Section: Synthetic Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…This six-step strategy produced 8.3 mg L À1 (À)-epipodophyllotoxin with 10% conversion. 32 Besides enzyme engineering and pathway optimization in vitro, engineering the supply and recycling of cofactors, which participate in many intracellular metabolic processes and reactions, is also a feasible way to enhance PTOX production. In 2022, on the basis of pathway optimization in yeast S. cerevisiae, ) reached gram-level production in the fedbatch fermentation, which has a considerable production potential at present 33 (Fig.…”
Section: Synthetic Biologymentioning
confidence: 99%
“…Natural Product Reports (À)-PTOX (Scheme 4). Researchers rst used the oxidative enolate coupling methodology to couple oxazolidinone (30) with an ester (31) to form a single diastereomer dibenzylbutyrolactone (32) as the natural substrate of the DPS enzyme. Then, they used chaperones GroEL and GroES to optimize the soluble expression level of the DPS enzyme, leading 32 to completely transform into (À)-DPS (19).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] In addition, Decembrino et al completely biosynthesized (À )-deoxypodophyllotoxin and (À )-epipodophyllotoxin in E. coli. [38] Moreover, Schultz et al also achieved milligram-level synthesis of (À )deoxypodophyllotoxin in tobacco. [39] The complete biosynthesis of PPT in plants was described in Scheme 10, phenylalanine (116) was deaminated by the action of phenylalanine ammonia lyase (PAL) to obtain cinnamic acid (117), followed by the formation of coniferaldehyde (118) catalyzed by seven enzymes, which was then converted to coniferyl alcohol (119) by the action of cinnamyl alcohol-dehydrogenase (CAD).…”
Section: Biotransformation Of Podophyllotoxin and Its Analoguesmentioning
confidence: 99%
“…Previous studies have suggested the potential capability of bacteria to produce lignans. Two sequential Escherichia coli lines, harboring individual metabolic modules of (-)-matairesinol to (-)-5′desmetyl-yatein, and (−)-5′desmetyl-yatein to (−)-deoxypodophyllotoxin, reportedly metabolized exogenously applied (-)-matairesinol to (-)-deoxypodophyllotoxin ( Decembrino et al., 2021 ). The human gut microbiome also metabolizes exogenously applied (+)-pinoresinol to various lignans ( Xie et al., 2003 ; Espín et al., 2017 ; Bess et al., 2020 ).…”
Section: The Heterologous Hostsmentioning
confidence: 99%